2020
DOI: 10.1186/s13023-020-01376-x
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review and proposed workflow for multi-omic rare disease research

Abstract: Background: Patients with rare diseases face unique challenges in obtaining a diagnosis, appropriate medical care and access to support services. Whole genome and exome sequencing have increased identification of causal variants compared to single gene testing alone, with diagnostic rates of approximately 50% for inherited diseases, however integrated multi-omic analysis may further increase diagnostic yield. Additionally, multi-omic analysis can aid the explanation of genotypic and phenotypic heterogeneity, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 139 publications
1
21
0
Order By: Relevance
“…Linkage analysis with candidate gene screening dominated the discovery of SCD genes in the past, often thanks to prior knowledge of these genes’ functions and expression profiles, their products, the pathways they serve, or pertinent animal models. WES is now dominating SCD gene discovery and we can expect that WGS will dominate the discovery of the genes causing Mendelian diseases in the future, probably within integrated multi-omics strategies to reduce the number of candidate variants ( Posey, 2019 ; Kerr et al, 2020 ).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Linkage analysis with candidate gene screening dominated the discovery of SCD genes in the past, often thanks to prior knowledge of these genes’ functions and expression profiles, their products, the pathways they serve, or pertinent animal models. WES is now dominating SCD gene discovery and we can expect that WGS will dominate the discovery of the genes causing Mendelian diseases in the future, probably within integrated multi-omics strategies to reduce the number of candidate variants ( Posey, 2019 ; Kerr et al, 2020 ).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…A holistic approach that integrates data obtained from multiple omics layers (multi-omics approach) has a higher biological reliability and can substantially enhance new Mendelian genes’ discovery than the single-omics approaches ( Labory et al, 2020 ). The multi-omics have been successfully used in many diseases, including neurological diseases, and is thus a promising approach to enhance the discovery of new SCD genes ( Crowther et al, 2018 ; Kerr et al, 2020 ; Labory et al, 2020 ).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Epigenetic signatures may display tissue specificity linked to disease mechanisms, however, obtaining kidney biopsy material is invasive and is not performed as part of routine clinical practice in people with DKD and T1D in the United Kingdom. Peripheral blood-based methylation biomarkers have shown promise in several clinical fields ( Moore et al, 2014 ; Agha et al, 2019 ; Cardenas et al, 2019 ; DiTroia et al, 2019 ; Henderson-Smith et al, 2019 ; Kerr et al, 2019a , b , 2020 ; Ladd-Acosta and Fallin, 2019 ; Zhou et al, 2019 ) including kidney disease ( Smyth et al, 2014b , 2018 ; Swan et al, 2015 ; Aranyi and Susztak, 2019 ; Gluck et al, 2019 ; Kato and Natarajan, 2019 ; Kerr et al, 2019b ; Park et al, 2019 ). We have previously demonstrated that blood-derived differential methylation is also reflected in kidney-derived differential methylation for CKD ( Smyth et al, 2014b ).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence for epigenetic phenomena has transformed investigations of heritable influences on disease and, complementary to genome-wide association studies (GWAS), it is now cost-effective to perform population-based studies of the epigenome (Rakyan et al, 2011b;Canadas-Garre et al, 2018;Kato and Natarajan, 2019;Kerr et al, 2020). Epigenetic modifications modulate gene expression without changing the DNA sequence; these may be either stably inherited or dynamic epigenetic marks.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of patient information available for research seriously hinders the diagnosis and treatment of rare and intractable diseases [7]. In general, RD patients suffer from very severe and heterogeneous symptoms and remain undiagnosed for several years [8]. Consequently, these disease communities use social media platforms to try to find other patients with similar health problems or expertise about their rare condition, sharing manifold types of information-including symptoms, treatments, side effects, and other diseases and activities-that go beyond what is normally captured in a clinical setting or patient registry [9].…”
Section: A Proof-of-concept Study Of Extracting Patient Histories Formentioning
confidence: 99%